Territorios de investigación - Curtis, William J. R. (El Croquis, 2003)
Comentarios acerca de las nuevas generaciones de arquitectos: <Abalos & Herreros>, <Mansilla + Tuñón Arquitectos>, <Foreign Office Architects>, <Díaz Moreno-García Grinda>, E. Arroyo, <NO.MAD Arquitectos, S.L.>, <Soriano-Palacios>, M. Ocaña, <Acebo-Alonso>, A. Payá, L. Alonso, J.García-Solera, J.D. Santos, <Nieto Sobejano Arquitectos>, <RCR Arquitectes>